Impact of Oil and Gas vs. Non-Oil and Gas Exports on Provincial Economic Growth: A Panel Data Analysis - Afliana, Mona; Zulham, Teuku; Suriani, Suriani; Miksalmina, Miksalmina (Graha Primera Saintifika, 2024)
Economic growth in Aceh Province, Indonesia, is expected to fluctuate due to the unstable growth rates of both oil and gas and non-oil and gas exports. This study aims to investigate the impact of these exports on economic growth in Aceh Province. Utilizing secondary data from the Statistics of Aceh Province (BPS Aceh), the study employed the panel regression method, specifically the random effect model, analyzing data from 23 districts/cities in Aceh Province over the period 2011-2022. Estimation results indicate that oil and gas export growth have a negative effect, while non-oil and gas export growth exerts a positive effect on economic growth in Aceh Province, both of which show robust statistical significance. Based on these empirical findings, it is suggested that there should be cooperation between the government and investors in Aceh Province to maximize the processing of oil and gas commodities for export, as well as to improve the quality of non-oil and gas commodities exported so that, in the future, the demand for non-oil and gas exports can remain stable, fostering sustainable provincial economic growth.